Pengembangan Media Powerpoint Materi Rasio Trigonometri Dengan Model Problem Based Learning di SMA Negeri 1 Klaten (JS (JURNAL SEKOLAH), 2021)
Abstract: Development of Media Powerpoint Material Trigonometric Ratio With Problem Base Learning Model in SMA Negeri 1 Klaten. This study aims to examine whether the learning media used in SMA Negeri 1 Klaten has been effective, able to lead learners to understand the existing material and contains the ability of the XXI century and what kind of mathematical learning media needs to be developed based on the material characteristics and characteristics of learners in order to be effective. The method used in this research is the Research and Development method, with a preliminary study conducted a survey through an online questionnaire in the form of Google Form by taking a sample of 60 learners and media utilization questionnaires to 72 students. The results of the initial study showed that students learned materials from various stand-alone learning media, namely package books, namely modules (72.22%), videos (90.74%) and Powerpoint (90.74%). The study also showed that students' problem solving skills were still low (57.41%). Learners want complete learning media, text, images and videos in one interactive multimedia and can be accessed at any time both offline and online. Learning media that needs to be developed according to the results of the initial research is Powerpoint with Problem Base Learning (PBL) learning model. Powerpoint developed and used in the learning process effectively improves the learning motivation and learning outcomes of learners.Keyword: powerpoint, problem based learning.Abstrak: Pengembangan Media Powerpoint Materi Rasio Trigonometri Dengan Model Problem Base Learning di SMA Negeri 1 Klaten. Penelitian ini bertujuan untuk meneliti apakah media pembelajaran yang digunakan di SMA Negeri 1 Klaten sudah efektif, mampu menuntun peserta didik untuk memahami materi yang ada serta memuat kemampuan abad XXI dan media pembelajaran matematika seperti apa yang perlu dikembangkan berdasar karakteristik materi dan karakteristik peserta didik agar efektif. Metode yang dipakai dalam dalam penelitian ini adalah metode Research and Development, dengan study pendahuluan melakukan survey melalui angket online berbentuk Google Form dengan mengambil sampel 60 peserta didik serta angket pemanfaatan media kepada 72 peserta didik. Hasil penelitian awal menunjukkan bahwa peserta didik mempelajari materi dari berbagai media pembelajaran yang berdiri sendiri-sendiri yaitu buku paket yaitu modul (72,22%), video (90,74%) dan Powerpoint (90,74%). Penelitian ini juga menunjukkan bahwa keterampilan pemecahan masalah peserta didik masih rendah (57,41%). Peserta didik menginginkan media pembelajaran yang lengkap, teks, gambar dan video dalam satu multimedia interaktif dan dapat diakses setiap saat baik secara offline maupun online. Media pembelajaran yang perlu dikembangkan sesuai hasil penelitian awal adalah Powerpoint dengan model pembelajaran Problem Base Learning (PBL). Powerpoint yang dikembangkan dan digunakan dalam proses pembelajaran efektifmeningkatkan motivasi belajar dan hasil belajar peserta didik .Kata kunci: powerpoint, pembelajaran berbasis masalah